1972
DOI: 10.1113/jphysiol.1972.sp009905
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sodium pump in squid axons by cardiac glycosides: dependence on extracellular ions and metabolism

Abstract: SUMMARY1. The rate of inhibition of the Na pump by ouabain was examined both by direct measurement of the rate of decline of the Na efflux and by the binding of [3H]ouabain.2. The onset of inhibition of the Na efflux was concentration-dependent; but did not follow simple first order kinetics. The time course of inhibition was roughly exponential although in about 30 % of the axons inhibition was preceded by a transient stimulation of the Na efflux.3. Inhibition of the Na efflux by both ouabain and strophanthid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 14 publications
7
31
2
Order By: Relevance
“…Even Li, which is known not to interfere with the inhibition of Na pump by ouabain (Gorman & Marmor, 1970;Baker & Willis, 1972), and can substitute for sodium as a carrier of inward current (Hille, 1970) and thus produce action potentials (Hodgkin & Katz, 1949;Huxley & Stampfli, 1951), failed to completely substitute for Na. A certain amount of Na was always required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even Li, which is known not to interfere with the inhibition of Na pump by ouabain (Gorman & Marmor, 1970;Baker & Willis, 1972), and can substitute for sodium as a carrier of inward current (Hille, 1970) and thus produce action potentials (Hodgkin & Katz, 1949;Huxley & Stampfli, 1951), failed to completely substitute for Na. A certain amount of Na was always required.…”
Section: Discussionmentioning
confidence: 99%
“…6). This suggests that Li can substitute for Na in the ouabain action (Gorman & Marmor, 1970;Baker & Willis, 1972). Accordingly, the effect of Li on the noradrenaline output induced by the reintroduction of Ca in the presence of ouabain was studied.…”
Section: Methodsmentioning
confidence: 99%
“…They also have a different localization in cells: α 1 is ubiquitously distributed over the surfaces of cells, while high ouabain affinity isoforms are confined to a reticular distribution within the cellular membrane that paralleled underlying endoplasmic or sarcoplasmic reticulum, with Na + /Ca 2+ exchanger protein. The expression of these isoforms is age-dependent [20][21][22][23][24][25]. While the role of low-affinity receptors as a working molecule for Na + /K + pump is well established [25][26][27], the functional role of high-affinity receptors is still discussable [13].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of these isoforms is age-dependent [20][21][22][23][24][25]. While the role of low-affinity receptors as a working molecule for Na + /K + pump is well established [25][26][27], the functional role of high-affinity receptors is still discussable [13]. Detailed investigations [28][29][30] showed that Na + / Ca 2+ exchange is regulated through the high-affinity ouabain receptors, while Na + /K + pump by means of low-affinity ones.…”
Section: Introductionmentioning
confidence: 99%
“…Both were equally effective suggesting that failure of glycoside to bind to the pump (cf. Baker & Willis, 1972;Sachs, 1974) was not a contributory factor. Raising [K]o to 15 mm, to ensure that the sodium pump was fully activated despite the low concentration of sodium, had no effect on the consequences of sodium removal for neural differentiation.…”
Section: Resultsmentioning
confidence: 95%